A nine-level hybrid current source inverter using common-emitter topology and inductor-cell - Suroso Suroso; Daru Tri Nugroho; Toshihiko Noguchi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
A different circuit structure of nine-level current source power inverter is presented and discussed in this manuscript. The proposed topology is based on the common-emitter inverter topology equipped with an inductor-cell circuit. The common-emitter inverter works as the main inverter circuits delivering a three-level AC current waveform. The inductor-cell circuit produces the intermediate output current levels for nine-level current output waveform. Proportional integral current controller was applied to regulate the current streaming thru the inductor-cell. Multi triangular carrier signals based sinusoidal pulse width modulation method was utilized to obtain a lower waveform distortion. The proposed nine-level inverter circuit was tested and examined. The test results verified that the new nine-level inverter circuit worked well producing a nine-level current waveform with less low-frequency harmonic components.